Numerical Analysis on the Scale Effect of a Free-Running Ship’s Manoeuvring Characteristics - Woo-Seok Choi; Gyeong-Seo Min; Hae-Chan Yun; Young-Uk Do; Kang-Min Kim; Momchil Terziev; Saishuai Dai; Daejeong Kim; Doojin Jung; Soonseok Song (Journal of Marine Science and Engineering, 2025)
This study focuses on the manoeuvring characteristics of model- and full-scale ships. Various methods, including free-running model tests (FRMTs), computational fluid dynamics (CFD), and theoretical approaches, were employed to estimate ship manoeuvring performance. However, these methods are typically simulated at model-scale, which introduces discrepancies in the Reynolds number due to Froude scaling laws. Although numerous studies have investigated scale effects, most have concentrated on ship resistance, with limited research on manoeuvring performance. To address this gap, this study developed a free-running CFD simulation model for both a model-scale and full-scale ONRT. The study involved a detailed analysis of manoeuvring trajectories, forces, and moments. This analysis aimed to highlight differences in manoeuvring performance caused by Reynolds number discrepancies between model- and full-scale ships, providing a quantitative assessment of performance variations across scales and contributing to a more accurate understanding of manoeuvring characteristics at full scale.